The Political Law of Simultaneous General Elections as Effort to Strengthen the Presidential System - Kusriyah, Sri; Ma'ruf, Umar; Rhodiyah Dwi Istinah, Siti; Witasari, Ariyani (Jurnal Daulat Hukum, 2024)
This study aims to analyze the legal politics of simultaneous general elections as an effort to strengthen the presidential system both under national and Islamic law, which aims to discuss how the legal politics of general elections in Indonesia is the embodiment of popular sovereignty. The method used in this paper was a normative juridical method, namely by analyzing the norms related to the holding of simultaneous general elections, so that the data used in this paper is secondary data, problem analysis using qualitative analysis. The results of the discussion show that the legal politics of simultaneous general elections is intended to emphasize a strong and effective presidential government system, and basically, Islam cannot be separated from politics as a form of practicing shura, Amar Ma'ruf Nahi Munkar, as well as fighting for justice and preaching good deeds. The MPR as the institution authorized to stipulate and amend the Constitution can make stipulations on guidelines for the implementation of development that must be carried out by the President, which will later serve as suggestions for evaluating the performance of the President for five years.